Dueto em três vozes : discursos historiográficos e estéticos do gaúcho em "O Laçado" e "El Gaucho Oriental" - Lima, Henrique Pereira (2012)
The aesthetics of the gaucho, produced by imaginary Rio Grande and Uruguay over the nineteenth and twentieth centuries, the agent inserts historical and social, within another structure - the symbolic. The time history, accordingly, intersects with the symbolic time, the construction of a third dimension, time direction, inside which the Gaucho is inserted and from which, relates to the demands more these large companies. The fluidity of political borders installed in Silver, urged the consolidation of nationalities Argentine, Brazilian and Uruguayan over the nineteenth and twentieth centuries mechanisms that ensure the delimitation of its sovereignty. In this sense, the construction of imaginary nationalism and historiography, to occupy themselves with this task, converged to construct an aesthetic particularity this agent and that this area since colonial times, showed signs of convergence. While the historical aspects have not been abandoned, its appropriation was guided by contemporary social interests, giving shape to the idealized and mythical "national gauchos", then taken as promoters of space occupation and founders of a story homeland. Cultural identities and political identities were structured by these criteria. In the story, this context already widely researched and debated, reveals new aspects, especially when the lenses through which the formation of nations in the region are compared platinum, are plural. The different artistic manifestations of these companies present themselves as exemplary field of action and interaction of different elements and different social subjects, formed a system of varied representations of the gaucho. This ability of art to express an objective content attributes to monuments "El Gaucho Eastern" and "The Laçador", installed in Porto Alegre - RS function to present the speech - so knowable - of different cultural identities that have shaped - and Uruguayan Rio Grande, respectively. These monuments, linked to different discourses about the gaucho express imaginary committed to various claims that even linked to aesthetics, do not lose their effectiveness discourse in society that the deeds or the host.